Fiscal effects of tariff reduction in the Caribbean Community - Peters, Amos ([s.n.] [S.l.], 2002)
Explores the fiscal effects of tariff reduction for the Caribbean Community. Concludes that Caribbean countries are likely to experience short-run revenue shortfall as a consequence of trade liberalization.